Simulation and analysis performance of turbo codes and convolutional codes using BPSK modulation technique in WCDMA environment / Siti Shuhada Othman - Othman, Siti Shuhada
This project illustrates the analysis performance of BPSK modulation between Convolutional Code and Turbo Code in WCDMA by using simulation technique. In this project, the WCDMA system is considered and the performance of both codes is investigated. Turbo Code and Convolutional Code are use to encode and decode the digital signal of the signal before modulation and after modulation process. The main objective is to compare the performance between both codes for digital communication system. The analysis performance is evaluated by means of bit error rates comparison of BPSK modulation between these codes in AWGN channel for WCDMA applications. This project is simulated by using MATLAB version 7.6.